Addressing the Question, What Is a Substorm?: 11th International Conference on Substorms (ICS‐11); Lüneburg, Germany, 2–7 September 2012. (26th February 2013) - Narita, Yasuhito; Glassmeier, Karl‐Heinz; Donovan, Eric
Abstract : Never in the history of magnetospheric research have there been more exciting opportunities to unravel the physical processes causing the most spectacular phenomenon in Earth's magnetosphere—the magnetospheric substorm. The four Cluster and the five Time History of Events and Macroscale Interactions during Substorms (THEMIS) spacecraft, together with new ground magnetometer arrays, ionospheric radar systems, and optical networks, provide detailed observations of the complex dynamical features of the magnetosphere. The 11th International Conference on Substorms (ICS‐11), sponsored by the German National Academy of Sciences Leopoldina, was held as a platform for the space plasma community to exchange recent discoveries in observations and theories.